Analisis Tentang Pengaruh Intensitas Cahaya pada Pertumbuhan Kacang Hijau (Vigna Radiata) - Fata, Raihan Alimul; Prayogo, Muhammad Suwignyo; Febrian, Valentino Rahma; Nurohim, Ahmad (STKIP HARAPAN BIMA, 2025)
This study aims to describe the implementation of the Problem-Based Learning (PBL) model in fostering critical thinking skills among third-grade elementary school students on the topic of metamorphosis. This research employs a qualitative descriptive approach with a descriptive study design. The research subjects consisted of 29 male students from Grade III of SD Aulia Cendikia Islamic School. Data were collected through direct observation, documentation, interviews, and student reflections. Data analysis utilized Miles and Huberman’s interactive analysis model, which includes three stages: data reduction, data display, and conclusion drawing. In the data display stage, the findings were presented in the form of descriptive narratives, tables, and direct quotations from students or teachers. Meanwhile, the conclusion drawing stage was conducted by examining the relationship between the implementation of the PBL model and the emergence of students’ critical thinking responses during the learning process. The results of the study indicate that the implementation of the PBL model positively influenced the development of students’ critical thinking skills. This can be seen from the students’ ability to identify, analyze, and find solutions to the given problems. The model also successfully enhanced students’ understanding of the learning material. Therefore, PBL proved to be an effective approach in shaping active, independent, and critical-thinking students.